Enhancing shopping centers’ media visibility - Pedreño-Santos, Ana (European Public & Social Innovation Review, 2024)
Introduction: In times of crisis such as a war, pandemic or meteorological hazard, companies face a double challenge: communicating with the consumer both from a commercial point of view and communicating to the consumer the instructions to follow derived from the risk situation. This research provides a conceptual and managerial overview of the components generating media impact in times of health crisis. Methodology: First, seventeen components are identified and grouped in three dimensions: content, format and organisation. We study the communication strategy of four shopping centres during the week of the reopening of the shopping centres after the COVID-19 pandemic lockdown of March-May 2020 in Madrid, Spain. Second, 164 news stories are analysed with a panel of experts and a principal component analysis, to determine the components of communication that present higher impact on media Results: Shopping centres media visibility in times of crisis, increase by using intuitive content that generates learning and security, in a format that details instructions clearly. Conclusions: It is a must for companies to have previously worked on building credibility and brand awareness, in order get space in media during crisis periods.